Adverse Local Tissue Reaction and Osteolysis After Ceramic-on-Ceramic Total Hip Arthroplasty - Yogen Thever, MBBS, MRCS (Edinburgh); Lynne Goh, MBBS, FRCPath, FRCPA; Sam Fong Yau Li, PhD, DSc, FRSC; Dahlia Ho Siu Ling, Bsc; Sean Yi Rong Chia, Bsc (Hons); Moo Ing How, MBBS, MRCS (Ireland), MMed (Ortho), FRCS (Arthroplasty Today)
Adverse local tissue reaction (ALTR) and osteolysis formation are more frequently described complications after total hip arthroplasty (THA) with metal-on-metal bearings. In this report, we present a unique case of ALTR and osteolysis formation with ceramic-on-ceramic bearing THA, which has been less commonly described in the existing literature. This rare case occurred in a 54-year-old patient who had a primary THA done 17 years prior to representing to our institution. As part of the workup for our patient to find out the underlying cause of his complications, we have carried out extensive investigations that have not been previously reported. We conclude that ceramic bearings in THA may not be entirely inert and may cause complications such as osteolysis and ALTR.